2017
DOI: 10.1007/s00223-017-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Ibandronate Maintains Bone Mass, Bone Structure, and Biomechanical Strength of Trabecular and Cortical Bone After Discontinuation of Parathyroid Hormone Treatment in Ovariectomized Rats

Abstract: Although parathyroid hormone (PTH) expresses an anabolic effect on bone mass, the increased bone mass disappears once PTH treatment is withdrawn. Therefore, sequential treatment with anti-bone-resorptive agents is required to maintain bone mass after PTH treatment. We examined the effect of sequential treatment with ibandronate (IBN), a nitrogen-containing bisphosphonate, following PTH in ovariectomized (OVX) rats. Wistar-Imamichi rats (27 weeks old) were ovariectomized and treated with PTH (10 µg/kg, s.c.; 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Although the dosage of PTH in this study was lower than that of other groups [27,28], we select this dose as a suitable dose to evaluate the bone volume or strength in OVX rats. Indeed, our previous studies using same PTH doses with this study, BV/TV in PTH group were almost same as Sham group [13,29]. The difference of age of rats or experimental condition might influence to the anabolic effects of PTH.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Although the dosage of PTH in this study was lower than that of other groups [27,28], we select this dose as a suitable dose to evaluate the bone volume or strength in OVX rats. Indeed, our previous studies using same PTH doses with this study, BV/TV in PTH group were almost same as Sham group [13,29]. The difference of age of rats or experimental condition might influence to the anabolic effects of PTH.…”
Section: Discussionsupporting
confidence: 65%
“…Several reports have demonstrated the usefulness of sequential treatment with anti-bone-resorptive agents such as SERMs or bisphosphonate after PTH treatment in animal models [11,12]. We also reported that ibandronate, a nitrogen-containing bisphosphonate, suppressed bone turnover and maintained BMD in ovariectomized (OVX) rats that had been pretreated with PTH [13].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nine-week-old female Wistar rats either underwent an ovariectomy (OVX) or Sham operation. The rats were divided into the following groups with eight to nine animals each and treated from 4 weeks after operation (13 weeks old): Sham group (Sham operated), OVX group, PTH group (OVX administered 10 µg/kg/day of hPTH(1-34) five times per week; the dosage of the drug was decided according to the previous reports [20][21] ) (Peptide Institute Inc., Osaka, Japan), eldecalcitol group (OVX administered 20 ng/kg/day of eldecalcitol five times per week, as reported by Takeda et al 22 ), or a combined group (OVX administered 10 μg/kg/day of hPTH(1-34) and 20 ng/kg/day of eldecalcitol for 4 or 8 weeks). This study was performed according to the experimental protocol approved by the Institutional Animal Care and Use Committee at Chugai Pharmaceutical Co., Ltd.…”
Section: Animals and Tissue Preparationmentioning
confidence: 99%
“…Osteoporosis treatment agents may alter cortical bone matrix. This can be inferred from measurements of ultimate stress ( Ardawi et al, 2016 ; Wang et al, 2011 ; Bahar et al, 2016 ; Takeda et al, 2017 ), a whole bone biomechanical strength endpoint that indirectly reflects bone material properties including those of bone matrix, and more direct methods such as nanoindentation testing ( Yang et al, 2013 ; Brennan et al, 2009a ) and FTIRI (Fourier transform infrared imaging) ( Gamsjaeger et al, 2011 ). Separate studies report that osteoporosis treatment agents can also alter the bone response to mechanical loading ( Roberts et al, 2009 ; Hagino et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%